Macroporous layers formation on n-Si substrates in an HF-containing electrolyte adding HCl - V. V. Bolotov; K. E. Ivlev; I. V. Ponomareva (Омский научный вестник)
Adding an oxidizing agent to a solution of hydrofluoric acid significantly changes the process of electrochemical etching, because allows to accelerate the dissolution of electron silicon. In this work, we studied the formation process and morphology of macropores in high-resistance n-Si depending on the concentration of HCl in the HF: C2 H5 OH electrolyte. It is shown that the presence of HCl leads to a more uniform pore diameter distribution both at the surface and in the layer depth, and the increase in etching rate. With an increase in HCl concentration, a narrower pore diameter distribution is observed; the main pores near the surface approximate in size to the pores in the depth of the porous layer. The results are explained by the action of HCl as an oxidant.